THE EFFECT OF USING WORDWALL LEARNING MEDIA ON STUDENT LEARNING OUTCOMES AT SMK BABUNNAJAH MENES PANDEGLANG - Ade Sofyan (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
Good learning can be seen from the classroom atmosphere and the interaction between teachers and students. The use of conventional and unvaried learning media causes students to lose enthusiasm and affects their learning outcomes. This study aims to determine the effect of Wordwall learning media on student learning outcomes in the periodic table of elements. This research used a quasi-experimental method with a nonequivalent control group design. Sampling was conducted using purposive sampling with a sample size of 60 students from SMK Babunnajah Menes Pandeglang in the 2024/2025 academic year, consisting of 30 students from X Farmacy A in the experimental class and 30 students from X Farmacy B in the control class. Data were collected using objective test questions to measure learning outcomes on the periodic table of elements. The results showed an increase in student learning outcomes after learning using Wordwall, with the average post-test scores for the experimental class being 80.15 and for the control class being 70.15. The results of the hypothesis test using the Mann-Whitney test showed a Sig (2-tailed) value of 0.003. This Sig (2-tailed) value is < ? (0.05). This means that there is a significant difference in post-test scores between the experimental class and the control class. It can be concluded that the Wordwall learning media has an effect on student learning outcomes in the periodic table of elements material.